2014
DOI: 10.1007/s00484-014-0887-4
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation in coat characteristics, tick loads, cortisol levels, some physiological parameters and temperature humidity index on Nguni cows raised in low- and high-input farms

Abstract: Seasonal variations in hair length, tick loads, cortisol levels, haematological parameters (HP) and temperature humidity index (THI) in Nguni cows of different colours raised in two low-input farms, and a commercial stud was determined. The sites were chosen based on their production systems, climatic characteristics and geographical locations. Zazulwana and Komga are low-input, humid-coastal areas, while Honeydale is a high-input, dry-inland Nguni stud farm. A total of 103 cows, grouped according to parity, l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 44 publications
2
14
0
Order By: Relevance
“…There is a scant amount of data in the literature on tick burden in cattle for tropical regions in the Americas. Most studies on this topic have been carried out in subtropical countries such as South Africa [8, 15], countries with extreme high temperatures such as Egypt [16] and Pakistan [17], and some tropical countries such as Tanzania [18] and Nigeria [21]. Tick burden is frequently reported using transformed data, which makes result comparison for actual tick burden difficult to interpret.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…There is a scant amount of data in the literature on tick burden in cattle for tropical regions in the Americas. Most studies on this topic have been carried out in subtropical countries such as South Africa [8, 15], countries with extreme high temperatures such as Egypt [16] and Pakistan [17], and some tropical countries such as Tanzania [18] and Nigeria [21]. Tick burden is frequently reported using transformed data, which makes result comparison for actual tick burden difficult to interpret.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Asmaa et al [16] found that the lowest number of ticks were observed around the eyes, neck and chest. Ticks prefer hidden and warm anatomical zones on the animal body [8]. Hence, a suitable environment for tick survival is under the tail and perineum, possibly explaining the high number of ticks observed on these body zones.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations